Germ line ERG haploinsufficiency defines a new syndrome with cytopenia and hematological malignancy predisposition - Zerella, Jiarna R.; Homan, Claire C.; Arts, Peer; Lin, Xuzhu; Spinelli, Sam J.; Venugopal, Parvathy; Babic, Milena; Brautigan, Peter J.; Truong, Lynda; Arriola-Martinez, Luis; Moore, Sarah; Hollins, Rachel; et al. (Blood, 2024)
The genomics era has facilitated the discovery of new genes that predispose individuals to bone marrow failure (BMF) and hematological malignancy (HM). We report the discovery of ETS-related gene (ERG), a novel, autosomal dominant BMF/HM predisposition gene. ERG is a highly constrained transcription factor that is critical for definitive hematopoiesis, stem cell function, and platelet maintenance. ERG colocalizes with other transcription factors, including RUNX family transcription factor 1 (RUNX1) and GATA binding protein 2 (GATA2), on promoters or enhancers of genes that orchestrate hematopoiesis. We identified a rare heterozygous ERG missense variant in 3 individuals with thrombocytopenia from 1 family and 14 additional ERG variants in unrelated individuals with BMF/HM, including 2 de novo cases and 3 truncating variants. Phenotypes associated with pathogenic germ line ERG variants included cytopenias (thrombocytopenia, neutropenia, and pancytopenia) and HMs (acute myeloid leukemia, myelodysplastic syndrome, and acute lymphoblastic leukemia) with onset before 40 years. Twenty ERG variants (19 missense and 1 truncating), including 3 missense population variants, were functionally characterized. Thirteen potentially pathogenic erythroblast transformation specific (ETS) domain missense variants displayed loss-of-function (LOF) characteristics, thereby disrupting transcriptional transactivation, DNA binding, and/or nuclear localization. Selected variants overexpressed in mouse fetal liver cells failed to drive myeloid differentiation and cytokine-independent growth in culture and to promote acute erythroleukemia when transplanted into mice, concordant with these being LOF variants. Four individuals displayed somatic genetic rescue by copy neutral loss of heterozygosity. Identification of predisposing germ line ERG variants has clinical implications for patient and family diagnoses, counseling, surveillance, and treatment strategies, including selection of bone marrow donors and cell or gene therapy.
Gesehen am 10.09.2025